Megaptera novaeangliae (humpback whale) - MH-05604 - Moore, Michael J.; Taylor, David B. (Woods Hole Oceanographic Institution, 2022)
Megaptera novaeangliae (humpback whale) - MH-05604 - male - 11.00 m - Pelvic location - unknown